Tertiary institution students' perceived preparedness to adopt mobile-learning technology (MLT) innovation in south western, Nigeria (2020)
Modern telecommunication technology devices, tools and applications have become mobile-learning (m-learning) platforms for learning and innovative teaching strategies. Such technologies are adaptable to tertiary education for both open and distance learning (ODL) as well as blended learning in the conventional school environment. However, it has been observed that most tertiary institutions are still engrossed in face-to-face teaching and learning approaches in a situation where most of the students are perceived to be digital natives with perceived high potentials for technology adoption. Therefore, this study investigated tertiary institution students' perceived preparedness to adopt mobile-learning technology (MLT) innovation in South-Western, Nigeria. The study adopted ex-post facto research design of descriptive survey type; it involves a total sample of450 tertiary institution students from three public institutions in Oyo State. Data was collected using a duly validated researcher-designed instrument titled 'Tertiary Institution Students Mobile-Learning Questionnaire' (TISMLQ) r=0.84; it measures students' self-efficacy on use of mobile technology and level of preparedness towards mobile-learning technology (MLT) adoption. Data collected was analysed using descriptive and inferential statistics. Findings revealed perceived high self-efficacy on use of mobile technology and very high rate of mobile phone-ownership especially, the use of smart phones. The study concludes that tertiary institution students in Nigeria SouthWestern states are highly prepared to adopt mobile-learning technology. Hence, we recommend that tertiary institution lecturers should explore curriculum integration of mobile-learning, while students should channel mobile phone use towards academic activities. Lastly, workable institutional Information Technology (IT) policy should be implemented by tertiary institutional leaders in South-Western Nigeria